2019
DOI: 10.15252/embr.201845907
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase PHF2 activates CREB and promotes memory consolidation

Abstract: Long‐term memory formation is attributed to experience‐dependent gene expression. Dynamic changes in histone methylation are essential for the epigenetic regulation of memory consolidation‐related genes. Here, we demonstrate that the plant homeodomain finger protein 2 (PHF2) histone demethylase is upregulated in the mouse hippocampus during the experience phase and plays an essential role in memory formation. PHF2 promotes the expression of memory‐related genes by epigenetically reinforcing the TrkB–CREB signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Some loci that positionally mapped (2-kb windows; 1-kb window on both sides to capture cis-regulatory effects) 19 to genic regions have prior evidence of involvement in GAD ( e . g ., PHF2 -rs12376738 and resistance to depression- and anxiety-like symptoms 20 and memory consolidation 21 ), PTSD ( e . g ., IL2 -rs45510091 and low dose cytokine treatments to reverse anxious symptoms), or related symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Some loci that positionally mapped (2-kb windows; 1-kb window on both sides to capture cis-regulatory effects) 19 to genic regions have prior evidence of involvement in GAD ( e . g ., PHF2 -rs12376738 and resistance to depression- and anxiety-like symptoms 20 and memory consolidation 21 ), PTSD ( e . g ., IL2 -rs45510091 and low dose cytokine treatments to reverse anxious symptoms), or related symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…This result is interesting since we found that haploinsufficiency of Kdm3b impairs, rather than enhances, motor memory. A recent study showed that another H3K9 demethylase, plant homeodomain finger protein 2 (PHF2), acts as a positive regulator of hippocampal memory without affecting amygdala-dependent cued fear memory [ 47 ], suggesting that each histone demethylase may have a distinct role depending on brain regions and behavioral tasks. It would be interesting to examine the role of other histone-modifying enzymes, including LSD1, in cerebellar learning.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying better memory in high-rank mice led us to investigate the expression levels of memory-related genes in the hippocampus, one of the crucial brain regions for memory consolidation and storage 47 . The results of quantitative PCR showed that the social ranks were negative corrected with the expression levels of GRIN2B (NR2B) 48 , a subunit of NMDA receptor that improves synaptic plasticity and memory in neurons, and Phf2, a histone demethylase (Figure 2A and B).…”
Section: High-rank Mice Showed Higher Expression Levels Of Memory-related Genesmentioning
confidence: 99%
“…The negative correlation between ranks and Creb expression was also at the margin of statistical significance (Figure 2C). Phf2 and Creb have been reported to be involved in the TrkB-CREB signaling pathway for memory consolidation 47 . It is worth noting that other genes involved in this pathway, including Bdnf, Ntrk2 (TrkB), Cdk5, and Camk2, all showed decreasing trends with ranks, although the data is not statistically significant (Figure S3).…”
Section: High-rank Mice Showed Higher Expression Levels Of Memory-related Genesmentioning
confidence: 99%
See 1 more Smart Citation